Simple pulse microwave waveguide calorimeter with temperature sensor LM 35 - Linnik, A.F.; Zalesky, D.Yu. (Problems of Atomic Science and Technology, 2023)
The paper presents the construction of a storage-type waveguide calorimeter designed to measure the energy of a sequence of short microwave pulses. The radiation is absorbed by water or ethanol, then the temperature increase is recorded by the LM 35 sensor. When using 14 cm³ of water, the energy measurement range is 3…88 J, and when using ethanol 1.3…40 J. The calorimeter is simple, cheap, and reliable.